Examining interprofessional collaboration in oncogenetic service delivery models for hereditary cancers: a scoping review protocol - Maude Laberge; Jason Robert Guertin; Hermann Nabi; Karine Bouchard; Michel Dorval; Maria Eugenia Espinoza Moya; Julie Lapointe (BMJ Open)
Introduction In a context of limited genetic specialists, collaborative models have been proposed to ensure timely access to high quality oncogenetic services for individuals with inherited cancer susceptibility. Yet, extensive variability in the terminology used and lack of a clear understanding of how interprofessional collaboration is operationalised and evaluated currently constrains the development of a robust evidence base on the value of different approaches used to optimise access to these services. To fill in this knowledge gap, this scoping review aims to systematically unpack the nature and extent of collaboration proposed by these interventions, and synthesise the evidence available on their implementation, effectiveness and economic impact.Methods and analysis Following the Joanna Briggs Institute guidelines for scoping reviews, a comprehensive literature search will be conducted to identify peer-reviewed and grey literature on collaborative models used for adult patients with, or at increased risk of, hereditary breast, ovarian, colorectal and prostate cancers. An initial search was developed for Medline, Embase, CINAHL (Cumulative Index to Nursing and Allied Health Literature), Cochrane and Web of Science on 13 June 2022 and will be complemented by searches in Google and relevant websites. Documents describing either the theory of change, planning, implementation and/or evaluation of these interventions will be considered for inclusion. Results will be summarised descriptively and used to compare relevant model characteristics and synthesise evidence available on their implementation, effectiveness and economic impact. This process is expected to guide the development of a definition and typology of collaborative models in oncogenetics that could help strengthen the knowledge base on these interventions. Moreover, because we will be mapping the existing evidence on collaborative models in oncogenetics, the proposed review will help us identify areas where additional research might be needed.Ethics and dissemination This research does not require ethics approval. Results from this review will be disseminated through peer-reviewed articles and conferences.